Hydrogen bond-mediated pseudo-halide complexation for stable and efficient perovskite precursors and solar cells - Yong, Taeyeong; Choi, Seongmin; Kim, Soo-Kwan; Han, Sanghun; Seo, Gayoung; Kim, Hae Jeong; Park, Jin Young; Yu, Han Na; You, Hyung Ryul; Lee, Eon Ji; Lee, Gyudong; Lee, Wonjong; et al. (Royal Society of Chemistry, 2024)
The deprotonation of organic cations and oxidation of halide ions in perovskites are major degradation factors causing irreversible stability and efficiency loss in devices. To address these issues, we designed the 3-mercaptobenzoic acid (3-MBA) additive, which facilitates spontaneous deprotonation due to its carboxyl group and enables hydrogen bonding with formamidinium (FA+). Adding 3-MBA to the perovskite precursor solution inhibits both deprotonation of organic cations and oxidation of halide ions, thereby enhancing the stability of perovskite precursors and films at elevated temperatures. This approach also improves perovskite crystallinity and passivates halide-related defects through covalent bonding with uncoordinated lead. As a result, 3-MBA-treated inverted (p-i-n) solar cells achieve a power conversion efficiency (PCE) of 24.3%. Moreover, the unencapsulated 3-MBA-treated devices show impressive thermal stability with a T98 lifetime after 1740 hours at 85 degrees C under nitrogen conditions. Additionally, 140-day-aged perovskite precursors containing 3-MBA retain over 96% of their initial efficiency. We present an integrated stabilizing approach to manage both perovskite precursors and films through modification by hydrogen bonding-mediated complexation.